Stunting Knowledge on the Prevention of Babies with BBLR in the PKU Muhammadiyah Yogyakarta Hospital - Retno Mawarti (International Journal of Health Science and Technology, 2020)
One of the problems suffered by toddlers is stunting caused by low birth weight (LBW). The number of stunting incidents in Indonesia in 2016 was 27.5% (Ministry of Health, 2016), while the incidence of stunting in Yogyakarta in 2016 was 14.4% Stunting can lead to poor motor and mental development at an early age, as well as poor cognitive presentations and school presentations in advanced childhood (Nutrition Section of the DIY Health Office, 2014). One of the efforts to prevent stunting is to see the knowledge of mothers about stunting. The purpose of this study was to determine the Knowledge Description of Stunting Prevention in mothers with LBW children at PKU Muhammadiyah Hospital Yogyakarta. This research uses a descriptive quantitative method. The study population was mothers who had LBW children with a total sample of 25 respondents who were drawn using a purposive sampling technique. The research instrument used a questionnaire and the analysis used a percentage. The results of this study show that maternal knowledge about LBW in the moderate category is 14 (56%) and the poor category is 11 (44%). The maternal knowledge about stunting, in the good category is 209 (80%), and in the fair category is 5 (20%). The maternal knowledge on prevention of stunting in LBW babies in the good category is 22 (88%), and in the poor category is 3 (12%). In the future, it is hoped that mothers with low birth weight babies can increase their knowledge of stunting prevention.